A model for prioritisation of industrial air pollutants: Part I. Formulation - Puong, Ling Law; Gracie, S.C. Chong; Chee, Khoon Ng (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/